THE RELATION BETWEEN CONFIDENCE, PARENTS’ ATTENTION, CLASSMATE INTERACTIONS AND MATHEMATICS LEARNING OUTCOMES OF GRADE VIII - Widi Priyati Nugraheni; Edi Prajitno (Universitas Ahmad Dahlan, 2018)
Low students’ learning outcomes are related to many factors. Confidence, parents’ attention, and classmate's interactions are among them. This study aims to determine whether there are positive and significant relations between confidences, parents’ attention, classmate interactions, and mathematics learning outcomes of grade VIII students of SMP Muhammadiyah 2 Yogyakarta in the even semester of the academic year of 2016/2017. The population in this study were regular grade VIII students of SMP Muhammadiyah 2 Yogyakarta in 2016/2017, consisting of four classes with the total number of 115 students. Random sampling technique was applied to take the sample of this research, which is grade VIII students class C. The data on confidences, parents' attention, and classmate interactions were obtained through questionnaires. At the same time, the data of the mathematics learning outcomes were obtained through the test. The research instruments were tested using a validity test, differential test, and reliability test. Analysis prerequisite test includes normality, linearity, and independence test. Product moment and multiple linear regression analyses were used to analyze the data. The results show that there are positive and significant relations between confidence, parents' attention, and classmate interactions with mathematics learning outcomes of grade VIII students of SMP Muhammadiyah 2 Yogyakarta in the even semester of the academic year of 2016/2017. The results are evidence in Fcount Ftable which is 8,251 > 2,975 with R = 0,976 and R2 = 0.952 with , with RC = , RC = and RC = 30,934 , EC = , EC = and EC = .